Fattening Management of Independent Broiler Chicken Business (case study in a ranch owned by Mr. Andi Mukri in Anaiwoi Neighborhoods of Tanggetada District) - Ayu Wulandari; J. Junaedi; S. Suparman (Chalaza Journal of Animal Husbandry, 2019)
The research was conducted to find out maintenance management at the farms of Mr. Andi Mukri.  The research was conducted in July 2018.  Data were analyzed quantitatively and descriptively.  The parameters observed included feed consumption, harvest age, body weight gain, feed conversion ratio, and mortality.  The results showed that the broiler chicken farm business of Andi Mukri was an individual household business which kept as many as 500 birds with a cage size of 15 meters x 8 meters.  The average body weight on the 22nd days is 956,5 grams, and on the 42nd day, it reaches 4231,4 grams whereas, on the 35th day it is 175,4 grams/week and the 42nd day is 1115,8 grams/week.  FCR of 0,7 %, mortality 0,8 %, age of harvest begins on day 24 to day 42.